2016
DOI: 10.2174/1874210601610010395
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Collagen Matrix as a Substitute for Free Mucosal Grafts in Pre-Prosthetic Surgery: 1 Year Results From a Clinical Prospective Study on 15 Patients

Abstract: Background:The presence of keratinized tissue around dental implants is more than desirable either from a functional and aesthetic point of view, making soft tissue grafting a common practice in implant rehabilitation. Autogenous soft tissue grafting procedures are usually associated with high morbidity. Aim of this study was to assess the efficacy of a xenogeneic collagen matrix as a substitute for soft tissue grafting around dental implants.Methods:15 consecutive patients underwent a vestibuloplasty and graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The xenogeneic CM showed an ideal haemostatic effect with no excessive bleeding during surgery and no bleeding at all during post-operative period, similar to other techniques using absorbable collagen sponges in different kinds of treatments [ 31 ]. Furthermore, all grafted sites presented, when healing was completed, an optimal integration with the surrounding tissues, as stated by other authors in previous studies [ 15 17 ]. Rotundo an Pini-Prato observed the good esthetic of the CM also when used in the coverage of multiple gingival recession [ 32 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The xenogeneic CM showed an ideal haemostatic effect with no excessive bleeding during surgery and no bleeding at all during post-operative period, similar to other techniques using absorbable collagen sponges in different kinds of treatments [ 31 ]. Furthermore, all grafted sites presented, when healing was completed, an optimal integration with the surrounding tissues, as stated by other authors in previous studies [ 15 17 ]. Rotundo an Pini-Prato observed the good esthetic of the CM also when used in the coverage of multiple gingival recession [ 32 ].…”
Section: Discussionsupporting
confidence: 81%
“…The surgical procedure, as already described in a previous study, consisted in a standard apically positioned flap with subsequent apposition of the CM, performed under local anesthesia [ 17 ]. At first, a midcrestal incision was performed in the residual keratinized band and a split thickness flap was raised.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, histology analysis indicated a significant difference in comparison to the natural tissue [ 133 ]. To reduce scar retraction and enhance the healing process, a novel collagen matrix, Geistlich Mucograft ® (Geistlich Pharma AG, Wolhusen, Switzerland), was designed and evaluated as a replacement for autogenous tissue to increase the width of keratinized tissue and cover gingival recessions [ 134 , 135 , 136 , 137 , 138 ]. Clinical data indicated strong enhancement of the keratinized tissue width with similar outcomes in comparison to the FGG [ 139 , 140 , 141 , 142 ].…”
Section: Oral Soft Tissue Regeneration: Current Treatments and Limmentioning
confidence: 99%
“…Wound patches based on xenogeneic collagen have already been identified as a reliable treatment option [ 5 , 6 ]. In this context, it has been shown that collagen as a biomaterial supports the wound healing process due to its non-inflammatory properties and excellent biocompatibility and additionally collagen materials can promote epithelial regeneration [ 5 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%